Kreativitas Musrizal Pada Sanggar Seni Karang Taruna Dalam Mengembangkan Tari Piring Arak-Arakan Pada Masyarakat Nagari Batu Banyak Kabupaten Solok Provinsi Sumatera Barat - Antoni, Monicha; Syofia, Ninon; Hardi, Hardi; Riyanti, Eva (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to discuss Musrizal's Creativity at the Karang Taruna Art Studio in Developing the Arak-arakan Plate Dance in the Batu Banyak Nagari Community, Solok Regency, West Sumatra Province. The method used in this study is a qualitative method with a descriptive-analytical approach, namely describing real data as found in the field and then analyzing it in depth. This study uses theories or expert opinions including the opinion of Y Sumandiyo Hadi about dance forms, and the opinions of Conny R Semiawan and Surya Pena Gemilang about creativity. The results of this study indicate that this Arak-arakan plate dance as a form of entertainment developed by Tri Murni, agreed by traditional leaders and community leaders of Batu Banyak Nagari, to be performed during the bridal procession either from the house of the groom's bako (marapulai) or from the house of the bride's bako, (anak daro), can also be performed at the procession from the bride's house to the groom's house (marapulai).